1997
DOI: 10.1046/j.1469-8137.1997.00807.x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus allocation and utilization in three grass species with contrasting response to N and P supply

Abstract: SIJMM.ARYThe growth of the grass Brachypodium pinnatum (L,) Beauv. in Dutch nutrient-poor chalk grasslands increases with enhanced nitrogen supply, whereas other grass species also require an enhanced phosphorus supply for a similar response (e,g, Dactylis glomerata L.), or are competitively suppressed at any increase in nutrient supply (e.g. Briza media L.). We investigated whether this interspecific variation in response to N and P supply is caused by differences in P productivity (PP), i.e. the instantaneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 26 publications
(30 reference statements)
3
26
0
Order By: Relevance
“…LMA was twofold lower under high P supply in comparison with P-deficient conditions. High LMA is often associated with P deficiency because of high concentrations of nonstructural compounds (Rao et al, 1989;Ryser et al, 1997;de Groot et al, 2001). Variation in leaf thickness has been reported in response to changes in light intensity and nutrient availability (Witkowski & Lamont, 1991;Meziane & Shipley, 1999), but its functional determination as related to changes in environmental conditions is still unclear.…”
Section: Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…LMA was twofold lower under high P supply in comparison with P-deficient conditions. High LMA is often associated with P deficiency because of high concentrations of nonstructural compounds (Rao et al, 1989;Ryser et al, 1997;de Groot et al, 2001). Variation in leaf thickness has been reported in response to changes in light intensity and nutrient availability (Witkowski & Lamont, 1991;Meziane & Shipley, 1999), but its functional determination as related to changes in environmental conditions is still unclear.…”
Section: Treatmentsmentioning
confidence: 99%
“…Leaf morphological changes affect nutrient distribution per unit of leaf area, which, in turn, affects the productivity of nutrients allocated to leaves (Poorter & Evans, 1998). Ryser et al (1997) reported a close relationship between productivity of leaf P and the ability to distribute it over a large leaf area. Our results indicate that AMF colonization would affect such relationships through the improvement of the P status of the plants.…”
Section: Treatmentsmentioning
confidence: 99%
“…In a comparison of a fast-growing species (Dactylis glomerata) and a slow-growing species (Brachypodium pinnatum) that co-occur in many nutrient-poor calcareous grasslands, it was found that only the former developed thicker roots when grown under conditions of high N or P (Ryser et al, 1997).…”
Section: Root Diametermentioning
confidence: 99%
“…In search of an explanation for these field observations, a number of greenhouse experiments have been carried out to investigate the morphological and physiological responses of grassland plants to varying balances of N and P (Shaver and Melillo 1984;Ryser et al 1997;Güsewell 2005a;Macek and Rejmankova 2007). Short-term experiments show that adding N, leading to high N:P supply ratios, increases plant biomass, whereas adding P, leading to low N:P supply ratios, does not promote plant growth (Güsewell 2005c;Güsewell et al 2003).…”
Section: Introductionmentioning
confidence: 99%